2008
DOI: 10.1590/s0103-84782008000400027
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de ovelhas em lactação alimentadas com dietas contendo diferentes níveis de fibra em detergente neutro

Abstract: RESUMO O objetivo do trabalho foi avaliar o efeito do fornecimento de dietas com diferentes níveis de fibra em detergente neutro (FDN) sobre o comportamento ingestivo de ovelhas em lactação. Foram utilizadas 18 ovelhas 5/8 Ile de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
4
6
0
5
Order By: Relevance
“…The authors reported that this increase in NDF content of DDGS-containing diets was correlated with NDF from other nonforage sources (concentrated feed), mainly to DDGS. These facts are in agreement with the values observed in relation to the time spent on the activities of DMI, RUM, RES, WAI and OAC.According to Hubner et al (2008), an increase in the NDF content in total sheep rations altered the ingestive behavior in a quadratic way for the time spent on DMI, RUM, RES, and WAI. These authors reported that the time spent on DMI and RUM increased as the diet NDF level increased from 34% to 52% in the total ration, with maximum points estimated at 43.5% NDF.…”
supporting
confidence: 90%
“…The authors reported that this increase in NDF content of DDGS-containing diets was correlated with NDF from other nonforage sources (concentrated feed), mainly to DDGS. These facts are in agreement with the values observed in relation to the time spent on the activities of DMI, RUM, RES, WAI and OAC.According to Hubner et al (2008), an increase in the NDF content in total sheep rations altered the ingestive behavior in a quadratic way for the time spent on DMI, RUM, RES, and WAI. These authors reported that the time spent on DMI and RUM increased as the diet NDF level increased from 34% to 52% in the total ration, with maximum points estimated at 43.5% NDF.…”
supporting
confidence: 90%
“…É importante salientar que teores elevados de FDN na dieta poderiam limitar o CMS (Hübner et al, 2008), o que, provavelmente não ocorreu no presente experimento, pois, o processamento físico da torta de macaúba pode ter reduzido a efetividade da fibra e seu efeito sobre a ingestão de matéria seca.…”
Section: Resultsunclassified
“…As expected, the animals lie longer during the evening, because ruminants perform more rumination in this period of the day (Zanine et al, 2008;Hübner et al, 2008, Marques et al, 2012Oliveira et al, 2013).…”
Section: Discussionmentioning
confidence: 57%